Plasmids in Streptococcus lactis: evidence that lactose metabolism and proteinase activity are plasmid linked. - Efstathiou, J D (1976)
Populations of lactose positive (Lac+) and proteinase positive (Prt+) cells from Streptococcus lactis M18, C10, and ML3 grown at 39 degrees C gave rise to increasing proportions of Lac- Prt- clones. The deficiencies did not appear until after a number of generations at the elevated temperature, and the rate depended on the strain.Lac- Prt+ and Lac+ Prt- mutants were isolated after treatment with ethidium bromide. Plasmid deoxyribonucleic acid was isolated by cesium chloride-ethidium bromide equilibrium density gradient centrifugation from the parent cultures as well as from their Lac- Prt-, Lac- Prt+, and Lac+ Prt- mutants. Five distinct plasmid sizes of approximate molecular weights of 2,4, 8, 21, and 27 million were found in S. lactis C10, whereas the Lac- Prt- derivative lacked the 8- and 21-million-dalton plasmids, but the 8-million-dalton plasmid was present in the Lac-Att mutant. In S. lactis m18 five plasmids possessing molecular weights of about 2, 4, 10, 18 and 27 million were observed. The 10- and 18-million-dalton plasmids were not detected in the Lac- Prt- mutants, whereas the Lac- Prt+ derivative lacked only the 18-million-dalton plasmid and the Lac+ Prt- mutant lacked only the 10-million-dalton plasmid. In S. lactis ML3 five distinct plasmids, with approximate molecular weights of 2, 4, 8, 22, and 30 million, were present. The 8- and 22-million-dalton plasmids were not detected in the Lac- Prt- derivative, but the 8-million-dalton plasmid was present in the Lac- Prt+ mutant. The evidence suggests that lactose-fermenting ability and proteinase activity in these organisms are mediated through two distinct plasmids having molecular weights of 8 x 10(6) to 10 x 10(6) for proteinase activity and 18 x 10(6) to 22 x 10(6) for lactose metabolism.